The progeny [large type] : a novel - Lee, Tosca Moon (Center Point Large Print, 2017)
Emily Jacobs is the descendant of a serial killer. Now, she's become the hunted. She's on a quest that will take her to the secret underground of Europe and the inner circles of three ancient orders--one determined to kill her, one devoted to keeping her alive, and one she must ultimately save.